Extraction of Lysozyme from Chicken Albumen Using Polyelectrolyte Complexes. Issue 6 (8th December 2021) - van Lente, Jéré J.; Lindhoud, Saskia
Abstract: Cells use droplet‐like membrane‐less organelles (MLOs) to compartmentalize and selectively take‐up molecules, such as proteins, from their internal environment. These membraneless organelles can be mimicked by polyelectrolyte complexes (PECs) consisting of oppositely charged polyelectrolytes. Previous research has demonstrated that protein uptake strongly depends on the PEC composition. This suggests that PECs can be used to selectively extract proteins from a multi‐protein mixture. With this in mind, the partitioning of the protein lysozyme in four PEC systems consisting of different weak and strong polyelectrolyte combinations is investigated. All systems show similar trends in lysozyme partitioning as a function of the complex composition. The release of lysozyme from complexes at their optimal lysozyme uptake composition is investigated by increasing the salt concentration to 500 mm NaCl or lowering the pH from 7 to 4. Complexes of poly(allylamine hydrochloride) and poly(acrylic acid) have the best uptake and release properties. These are used for selective extraction of lysozyme from a hen‐egg white protein matrix. The (back)‐extracted lysozyme retains its enzymatic activity, showing the capability of PECs to function as extraction media for proteins. Abstract : Complexes made from oppositely charged polymers are used to selectively extract lysozyme enzymes from egg white. By decreasing the pH, the lysozyme can be recovered from the complex. After recovery, the lysozyme retains its enzymatic function.